Marietta Sadova: Fascist Identities and Political Compromise in Communist Romania - DĂLĂLĂU, Andrei (Studia Universitatis Babeș-Bolyai Historia, 2022)
After a brief period of liberalization in 1956, cultural politics in communist Romania went through an ideological radicalization between 1958 and the early 1960s, which led to intimidation campaigns, arrests, trials, and condemnations of several groups of interwar intellectuals. Director and actress Marietta Sadova was convicted in the 'Noica-Pillat' trial in March 1960. This paper aims to unravel the complex interaction between culture and politics through a qualitative analysis of Marietta Sadova's case study. The focus will be on the Securitate's surveillance, coercion methods, and narrative construction on one hand and the artist's surviving fascist identity, compromises made to survive, and the validity of cultural niches of existence on the other. The theoretical and methodological apparatus is built on new historiographical approaches to communist repression, including the ability of the secret police to construct and politically instrumentalize guilt narratives. The results suggest that the interaction between the interwar intellectuals and the communist authorities was neither unidirectional nor unitary but multi-layered and mutually depended on negotiations and concessions, as well as on the secret police agents' newly acquired methods of creating and repressing 'hostile' social networks. Article history: Received: 28.04.2022; Revised: 01.08.2022; Accepted: 01.08.2022; Available online: 15.09.2022 Rezumat: După o scurtă perioadă de liberalizare în 1956, politicile culturale din România comunistă au intrat într-o perioadă de radicalizare între 1958 şi începutul anilor 1960, care au dus la campanii de intimidare, arestări, procese şi condamnări politice ale diferitelor grupuri de intelectuali socializați în perioada interbelică. Marietta Sadova, director şi actor de teatru, a fost condamnată în procesul lotului „Noica-Pillat” în martie 1960. Articolul urmăreşte interacțiunea complexă dintre cultură şi politică în România anilor 1950 prin intermediul unei analize calitative asupra studiului de caz al Mariettei Sadova. Analiza se concentrează, pe de-o parte, pe tehnicile de supraveghere ale Securității, metodele coercitive aplicate şi construcția narativă a vinovăției, iar pe de altă parte se operează o deconstrucție a identității fasciste reziduale, a compromisurilor realizate şi a validității conceptului de nişte culturale ale existenței. Aparatul teoretic şi metodologic se fundamentează pe baza unor abordări istoriografice moderne ale represiunii comuniste, accentuând capacitatea poliției secrete de a construi şi instrumentaliza narațiuni ale vinovăției. Rezultatele studiului relevă faptul că interacțiunea dintre intelectualii interbelici şi autoritățile comuniste nu a fost nici unitară, nici unidirecțională, ci poate fi definită mai degrabă ca multistratificată şi dependentă reciproc de negocieri şi concesii, precum şi de noile metode ale agenților Securității de a inventa şi ulterior reprima rețele sociale „ostile”. Cuvinte-cheie: comunism, politici culturale, fascism, Marietta Sadova, represiune, teatru.